Impact of Capital Structure, Liquidity, and Company Size on Corporate Income Tax - Nadia Eka Pratiwi; Umaimah Umaimah (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2026)
This study aims to analyze the impact of capital structure, liquidity, and firm size on Corporate Income Tax in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The study employs a quantitative approach using secondary data obtained from companies’ annual financial statements. The sample was selected using purposive sampling, yielding 96 manufacturing companies with a total of 285 observations. Data analysis techniques include descriptive statistics, classical assumption tests, and multiple linear regression analysis to examine the effects of the independent variables on the dependent variable. The results indicate that capital structure has a negative and significant effect on Corporate Income Tax, suggesting that an increase in the proportion of debt in a company’s financing structure can reduce the tax burden through interest expenses that are deductible for tax purposes. Liquidity does not have a significant effect on Corporate Income Tax, indicating that a company’s ability to meet its short-term obligations does not directly influence the amount of tax payable. Meanwhile, firm size has a positive and significant effect on Corporate Income Tax, implying that companies with larger asset scales tend to incur higher tax burdens due to increased business activities and greater profit potential. The findings of this study contribute to the development of accounting and taxation literature and provide practical implications for corporate management in formulating financing policies and efficient tax planning strategies while remaining compliant with applicable tax regulations.